The Relevance of al-Ghazali’s Concept of Tazkiyatun Nafs in Strategies for Maintaining the Mental Health of Islamic Boarding School Students: A Literature Review - Saputri, Intan Nur Fauziah; Sa'diyah, Halimatus; Hasan Arwani, Nabil; Salsabila, Bilqist Adna; Qudsiyyah, Habibatul (Proceedings Conference Psychology and Flourishing Humanity; Vol 2 No 1 (2025): Proceedings Conference on Psychology and Flourishing Humanity, 2025)
Abstract The increasing mental health issues among Islamic boarding school students require preventive and curative maintenance strategies. This study aims to analyze the relevance of the concept of tazkiyatun nafs (purification of the soul) according to Al-Ghazali as a strategic framework for maintaining the mental health of Islamic boarding school students. Through a literature review, this study highlights how Al-Ghazali's emphasis on purification of the heart, control of desires, and strengthening of spiritual awareness can be an integrative solution in building psychological- -resilience. The results of the study show that Imam Al-Ghazali's concept of tazkiyatun nafs not only has a strong spiritual foundation but is also in line with contemporary approaches to mental health maintenance. Thus, this research study can be used as an important reference in formulating strategies for mental health sustainability in Islamic boarding schools.